Digital clubbing as the predominant manifestation of hypertrophic osteoarthropathy caused by pathogenic variants in HPGD in three Indian families. Issue 3 (July 2020) - Radhakrishnan, Periyasamy; Jacob, Prince; Nayak, Shalini S.; Gowrishankar, Kalpana; Prakash Soni, Jai; Shukla, Anju; Girisha, Katta M.
Abstract : 15-Hydroxyprostaglandin dehydrogenase is NAD + -dependent catalytic enzyme involved in prostaglandin biosynthesis pathway encoded by HPGD. The pathogenic variations in HPGD cause primary hypertrophic osteoarthropathy (PHO). The objective of the present study is to identify the genetic basis in patients with digital clubbing due to PHO. We performed detailed clinical and radiographic evaluation and exome sequencing in patients from three unrelated Indian families with PHO. Exome sequencing revealed two novel, c.34G>A (p.Gly12Ser) and c.313C>T (p.Gln105*) and a known variant, c.418G>C (p.Ala140Pro) in HPGD . Herein, we add three Indian families to HPGD mutation spectrum and review the literature on variants in this gene. Abstract : Supplemental Digital Content is available in the text.